2020
DOI: 10.1186/s12885-020-07097-5
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis as a poor prognostic predictor on postoperative survival of patients with solitary small hepatocellular carcinoma

Abstract: Background: Small hepatocellular carcinoma (sHCC) is a special subtype of HCC with the maximum tumor diameter ≤ 3 cm and excellent long-term outcomes. Surgical resection or radiofrequency ablation provides the greatest chance for cure; however, many patients still undergo tumor recurrence after primary treatment. To date, there is no clinical applicable method to assess biological aggressiveness in solitary sHCC. Methods: In the current study, we retrospectively evaluated tumor necrosis of 335 patients with so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 37 publications
6
33
0
1
Order By: Relevance
“…Our results showed that patients with high MD/TD were more likely to show MVI. HCC patients with vascular invasion have a poor prognosis [24], and our study con rmed that patients with high MD/TD were more likely to relapse compared with patients with low MD/TD (P<0.001). Wang et al reported that circulating tumor DNA correlates with MVI and predicts tumor recurrence of HCC [17].…”
Section: Discussionsupporting
confidence: 64%
“…Our results showed that patients with high MD/TD were more likely to show MVI. HCC patients with vascular invasion have a poor prognosis [24], and our study con rmed that patients with high MD/TD were more likely to relapse compared with patients with low MD/TD (P<0.001). Wang et al reported that circulating tumor DNA correlates with MVI and predicts tumor recurrence of HCC [17].…”
Section: Discussionsupporting
confidence: 64%
“…Tumor necrosis is an important hallmark of aggressive cancers and associated with poorer patient prognosis in different types of cancer ( 51 54 ). By using tumor spheroids, which mimic the 3D architecture of a tumor in vitro , we looked for the abundance of the central necrotic core with or without MB expression under both normoxia and 1% hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…For the tumor necrosis criteria, we considered a cutoff point ≤10% for classifying tumor as high or low in necrotic areas. After a complete assessment of the tumor bed, tumor necrosis areas with a histopathologic appearance of homogenous clusters of dead cells or cells organized into groups forming a coagulum containing cytoplasmic and nuclear debris, we quantified them as described in previous studies on other types of cancer [ 20 ] and classified them into one of the groups defined in our study.…”
Section: Methodsmentioning
confidence: 99%
“…However, histopathological investigation can provide much more valuable information regarding tumor cell architecture, stromal component, local immune response, and the presence of necrosis that might carry additional prognostic potential. These histopathological features have proven their predictive value in different types of cancers and are currently used in clinical practice [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%